Strains of Spodoptera frugiperda (J.E.Smith) (Noctuidae) in the states of Paraná and São Paulo, Brazil - Richardt, Francielly Silveira; Micheli, Adriana; Tasior, Daniele; Ruthes, Elderson; Foerster, Luís Amilton (EntomoBrasilis, 2020)
Two strains of Spodoptera frugiperda (J.E. Smith) were first described in the United States; in Brazil, in the states of Rio Grande do Sul, Mato Grosso, and western Paraná they have also been reported. This study was aimed at identifying these strains in Norte Pioneiro and Campos Gerais, in the states of Paraná and southwestern São Paulo. Larvae of S. frugiperda were collected in the cities of Ponta Grossa, Tibagi, Arapoti, and Wenceslau Braz in Paraná, and in the city of Itaberá, in São Paulo. PCR-RFLP genotyping of the COI gene was carried out using sixty-six specimens. Based on their electrophoretic pattern, 51 individuals were identified as corn strain, five as rice strain, and 10 as hybrids (Rice in MspI and Maize in SacI). Our findings indicate that both S. frugiperda strains are present the study areas.